PENGARUH FITUR, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE OPPO (Studi Kasus di Mentari Cell Jember) - Fitriani, Diana Novita; Fatimah, Feti; Izzudin, Ahmad (Growth, 2022)
The Oppo brand smartphone is quite well-known in the Jember area because for teenagers this brand has an affordable price and the benefits of the features that are obtained are sufficient for their daily needs. The results of the initial observation that Oppo is one of the products with high sales. This study aims to determine and identify the effect of price, features and promotions on purchasing decisions. This type of research is quantitative research and data collection techniques using observation, interviews and questionnaires to 106 respondents with sampling techniques, using non-probability sampling with a purposive sampling approach. The analytical tools used in this study are validity test, reliability test, classical assumption test, multiple linear regression analysis. The test results show that the price variable has no significant effect on product purchasing decisions at Mentari Cell Jember, feature variables have no significant effect on product purchasing decisions at Mentari Cell Jember and promotion variables have a significant effect on product purchasing decisions at Mentari Cell Jember. This proves that promotion can influence customer purchasing decisions, because with promotions the customer can determine the appropriate needs for himself.